Profile and Behaviour of Mother as Factor of Increasing Diarrhea Incidence Children Under Five at Jatinangor District in 2013 - Widhyasti, Rahayu; Arisanti, Nita; Rosalina, Ina (Althea Medical Journal, 2016)
Background: In 2012, data from Health Center of Jatinangor District showed nearly 50% of diarrhea cases occured in children under five at Sayang Village and Cilayung Village. Diarrhea cannot be separated from several factors that influence it, thus to reduce the incidence rate of diarrhea needs description of factors that affect diarrhea in children so that prevention can be done maximally. Objective of this study was to describe profile and behavior of mother as one factor of increasing diarrhea incidence in children under five at Jatinangor.Methods: This study was descriptive with cross-sectional design conducted at Sayang Village and Cilayung Village in OctoberâNovember 2013. The respondents of this study were 102 mothers who have infants aged 0â59 months thorough cluster sampling methods. Respondent will be interviewed and given validated questionnaire. Results: The result showed that 57.8% of mother aged 25â35 years, mostly graduated from junior high education (41.2%), and 81.4% as a housewife. Most of diarrhea occurred in children under 2 years and female. There were 73.5% mother who exclusively breastfed, 94.1% have good behavior of clean water usage, 61.8% with good hand washing behavior, and 60.8% respondents utilized healthy latrine.Conclusions: This study showed good results in behaviour of exclusive breastfeeding, behavior of clean water usage, behaviour of hand washing with clean and water flow, and behaviour of healthy latrine usage. Other factors might be contributed to increasing diarrhea incidence. [AMJ.2016;3(4):655â60]Â DOI:Â 10.15850/amj.v3n4.956